Meta-avaliação das políticas de cotas : um estudo de processos nas universidades estaduais paranaenses - Souza, Andreliza Cristina (Universidade Federal de São Carlos, 2018)
This thesis have accomplished a meta-evaluation of quota policies in Paraná’s state public universities. The general objective was to analyze the evaluations processes regarding the similarities and differences, potentialities and limits, as well as to verify which strategies and procedures were used more frequently for this kind of evaluation. The thesis is that the evaluation of quota policies has fragility in reason it is not carried out according to the theoretical and methodological foundations of the evaluation due to the political tension around the quotas. In order to base this research, discussions contemplated philosophical and epistemological assumptions of evaluating as a research field (AFONSO, 2009; FERNANDES, 2010; DIAS SOBRINHO, 2002; 2003a); definitions and interfaces between state and public policies were presented, and a brief discussion about the state as a provider versus a governor; the concepts of focal policies and affirmative actions were presented; and the influence of Durban Conference and its unfolding on expanding access to higher education. The instruments for collecting data were: documents – quota policy’s performance and evaluation processes; and interviews – actors enrolled in this context, systematized with content analysis method. For policy analysis was used the polity cycle (BOWE; BALL; GOLD, 1992; BALL; MAGUIRE; BRAUN, 2016), and has shown that: a) institutions analyzed had similar motives for vacancy reservations: institutional and social influences and the democratization of public schools; b) national debates about affirmative actions had great influence over these institutions; c) racism, conservative positions, resistance from institutions and/or actors and the reasoning that implies quality losses has made impossible to install racial quotas in three of the analyzed institutions; d) each institutions has defined their own model for policies; e) in some cases, the way the text was written limited access to black students or students from public schools. The meta-evaluation (SCRIVEN 2009; STUFFLEBEAM 1981; 2001; 2011; WORTHEN; SANDERS; FITZPATRICK, 2004) revealed that: a) two institutions did not carry out evaluation/monitoring, although there was a forecast of quota’s policy evaluation; b) these were evaluations of processes, of the ex-post kind, made by members of the institutions; c) the evaluators had a partial position in the realization of the evaluations; d) this bias, in the sense of confirmation of the policy, favored the debate on quotas, as well as its permanence as an access policy; e) the propensity of some actors to evaluate the quota policy in favor of their legitimation may have concealed relevant factors that have affected the effectiveness of this affirmative action; f) evaluations attended the criteria of precision, data importance, relevance and dissemination; g) criteria of reliability, credibility and cost x efficiency were not met. It was concluded that the evaluation process was feared by the institutions, specially by the actors involved in the approbation of policies, not effectively occurring for fear that the evaluation were be used as an instrument for denying quotas and reduce access in higher education. It is necessary to discuss quotas. Amongst the considerations stands out need to further discussions of quotas, qualify evaluation processes, to form technical staff, to develop methods and strategies suitable for different situations and knowledge production about evaluation as an epistemological field.
Meta-evaluation of quota policies : a study of processes in Paraná’s state public universities
Keywords: Universidades Públicas Paranaenses; Meta-avaliação; Ciclo de políticas; Política de cotas; Ensino superior; Meta-evaluation; Policy cycle; Quota policies; Higher education; Paraná’s Public Universities; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL